Optimal Taxation with Household Production. - Henrik Jacobsen Kleven; Wolfram F. Richter; Peter Birch Sørensen (University of Copenhagen, Economic Policy Research Unit (EPRU), 1999)
This paper suggests that the optimal tax system should favour market-produced services which are close substitutes for home-produced services. First, we modify the classical Corlett-Hague rule for optimal commodity taxation by showing that it may be optimal to impose a relatively low tax rate on consumer services even if such services are complements to leisure. Second, we find that when services and other goods are equally substitutable for leisure, so that uniform commodity taxation would be optimal in the absence of home production, the optimal tax structure will certainly involve a relatively low tax rate on consumer services.
Keywords: 330